2017
DOI: 10.1007/s00420-017-1245-8
|View full text |Cite
|
Sign up to set email alerts
|

Organic solvent exposure and depressive symptoms among licensed pesticide applicators in the Agricultural Health Study

Abstract: Purpose Although organic solvents are often used in agricultural operations, neurotoxic effects of solvent exposure have not been extensively studied among famers. The current analysis examined associations between questionnaire-based metrics of organic solvent exposure and depressive symptoms among farmers. Methods Results from 692 male Agricultural Health Study participants were analyzed. Solvent type and exposure duration were assessed by questionnaire. An “ever-use” variable and years of use categories w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…Among the developed country literature, United States studies have also studied links between pesticide exposure and farmer mental health. Some pesticides are neurotoxic, which are said to directly affect neural systems known to cause mental illness [108,109,110,111,112,113] and depression [56,60,64,65,70,72,74,114,115,116,117,118,119,120,121,122,123]. Some studies have examined pesticide exposure in general, while others considered specific compounds such as organophosphates.…”
Section: Systematic Review Resultsmentioning
confidence: 99%
“…Among the developed country literature, United States studies have also studied links between pesticide exposure and farmer mental health. Some pesticides are neurotoxic, which are said to directly affect neural systems known to cause mental illness [108,109,110,111,112,113] and depression [56,60,64,65,70,72,74,114,115,116,117,118,119,120,121,122,123]. Some studies have examined pesticide exposure in general, while others considered specific compounds such as organophosphates.…”
Section: Systematic Review Resultsmentioning
confidence: 99%
“…Feelings about the future affected work satisfaction: being depressed decreased it but being optimistic or feeling good increased satisfaction [32]. In addition, exposure to any solvent, gasoline, or petroleum distillates increased depression scores on the CES-D, but exposure to paint thinner did not have an effect [53]. Five correlates to conventional farmers' health were identified, two linked with emotions and three linked to pesticides.…”
Section: Correlates Of Organic Farmers' Healthmentioning
confidence: 96%
“…Similar to organic farmers, Rickson et al (1999) measured predictors of farmers' work satisfaction [32]. Siegel et al (2017) presented data about the effects of pesticide exposure on depression, measured by the CES-D [53].…”
Section: Correlates Of Organic Farmers' Healthmentioning
confidence: 99%
“…Because of its small size and lipid solubility, PCE easily crosses the blood brain barrier and selectively concentrates in the brain and other lipophilic tissue. Epidemiologic studies of adults with occupational exposure to PCE and related solvents have reported increases in anxiety and depression [8,9,11,[16][17][18] and impairments in cognition, memory, attention, executive function and trigeminal nerve and vestibular function [8][9][10][11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…Studies of adults exposed to PCE and related solvents in occupational settings have reported decrements in cognition, memory, attention, executive function, and trigeminal nerve and vestibular function [8][9][10][11][12][13][14][15]. Studies have also linked occupational exposure to increases in anxiety and depression [8,9,11,[16][17][18].…”
Section: Introductionmentioning
confidence: 99%